Replotting marriage in nineteenth-century British literature - Galvan, Jill Nicole, 1971-; Michie, Elsie B. (Elsie Browning), 1948- (The Ohio State University Press, 2018)
"This volume puts marriage in conversation with many aspects of culture--education, anthropology, Darwinism, crime, and more--widening the repertoire of questions scholars ask about fictional coupling. Attending closely to genre and narrative, it analyzes the marriage story as formally diverse rather than a familiar plot line"--